Perilaku Komunikasi dalam Proses Rehabilitasi Pecandu Narkoba di Rumah Sakit HB Sa’anin Padang - Neni Efrita; Eliza Eliza; Sulthan Jiyad Muqsid (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
The process of rehabilitation of drug addicts in the Psychiatric Hospital in addition to medical and social processes, rehabilitation of drug addicts at the HB Sa’anin Padang Hospital also has used various forms of communication behavior to restore the health of drug addicts. The process of integrated treatment and recovery activities will be carried out if health workers and psychologists are skilled in communicating both verbally and nonverbally. The formulation of the problem in this research is how communication behavior in the process of rehabilitation of drug addicts at the Mental Hospital HB Sa’anin Padang. With the methodological approach used is qualitative, data collection through observation, interviews and documentation. The results showed: 1. Verbal communication behavior in the process of rehabilitation of drug addicts at the HB Sa'anin Psychiatric Hospital in Padang carried out by health workers is verbal communication behavior in the form of verbal words and written words, written words are used as guides to act and act in the rehabilitation process. 2. The behavior of nonverbal communication in the process of rehabilitation of drug addicts in the Psychiatric Hospital HB Sa’anin by health workers with drug addicts is in the form of artifactual (appearance), proxemic (physical distance) and paralinguistic (intonation and tone of voice)